How Africa Should Engage Ubuntu Ethics and Artificial Intelligence - Simon K. Langat; Pascal M. Mwakio; David Ayuku (Journal of Public Health International, 2020)
Automation of human tasks has taken place for a long time now. Humans have in earlier periods dreamed of a world where machines capable of mimicking decision making would be created with some works of fiction describing in caricature, how machines would take over the human space in the world. Artificial intelligence has come to fruition in the last few decades following the development of fast computing capability and vast chip memory. Discussions of how the human space will look and feel when artificial intelligence have taken place at various levels of global organization geared towards ensuring that the new “thinking machines” do not rock human society in ways to render them obsolete. This article looks at the ethics of AI considering the issues that have been outlined by others in the light of communitarian ethics as seen in Africa. It describes the possible impact of thinking machines on society and how individuals would relate with each other and with AI systems.
Keywords: Automation